2019
DOI: 10.7554/elife.44986
|View full text |Cite
|
Sign up to set email alerts
|

Reduced metabolism supports hypoxic flight in the high-flying bar-headed goose (Anser indicus)

Abstract: The bar-headed goose is famed for migratory flight at extreme altitude. To better understand the physiology underlying this remarkable behavior, we imprinted and trained geese, collecting the first cardiorespiratory measurements of bar-headed geese flying at simulated altitude in a wind tunnel. Metabolic rate during flight increased 16-fold from rest, supported by an increase in the estimated amount of O2 transported per heartbeat and a modest increase in heart rate. The geese appear to have ample cardiac rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Regulated hypothermia (often referred to as anapyrexia) can be launched by birds facing other challenging conditions such as hypoxia and during daily torpor triggered by a seasonal decrease in food and/or water availability (McKechnie & Lovegrove, 2002;Butler, 2004;Bicego et al 2007;Ruf & Geiser, 2015;Amaral-Silva et al 2017;Meir et al 2019). Therefore, it is reasonable to hypothesize that regulated hypothermia occurs in birds severely challenged by pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Regulated hypothermia (often referred to as anapyrexia) can be launched by birds facing other challenging conditions such as hypoxia and during daily torpor triggered by a seasonal decrease in food and/or water availability (McKechnie & Lovegrove, 2002;Butler, 2004;Bicego et al 2007;Ruf & Geiser, 2015;Amaral-Silva et al 2017;Meir et al 2019). Therefore, it is reasonable to hypothesize that regulated hypothermia occurs in birds severely challenged by pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Under hypoxic conditions, oxygen and carbon dioxide metabolism mainly depend on mitochondrial respiration and make use of adenosine triphosphate (ATP). Recently, a number of studies have shown the key regulatory role of energy metabolism, including glucose, carbohydrate, and lipid metabolic processes, among others, during hypoxic adaptation [52][53][54][55]. In the current research, from the constructed ceRNA network, we identi ed seven differentially expressed miRNAs (novel-miR-819, novel-miR-676, novel-miR-85, novel-miR-693, novel-miR-775, novel-miR-669, and novel-miR-867) and sixteen differentially expressed genes related to energy metabolism including glycosylation, glucose metabolism process, carbohydrate metabolism process, fatty acid metabolism, and ATP binding.…”
Section: Discussionmentioning
confidence: 99%
“…Under hypoxic conditions, oxygen and carbon dioxide metabolism mainly depend on mitochondrial respiration and make use of adenosine triphosphate (ATP). At present, a number of studies have shown the key regulatory role of energy metabolism, including glucose, carbohydrate, and lipid metabolic processes, among others, during hypoxic adaptation [49][50][51][52]. In the current research, from the constructed ceRNA network, we identi ed seven differentially expressed miRNAs (novel-miR-819, novel-miR-676, novel-miR-85, novel-miR-693, novel-miR-775, novel-miR-669, and novel-miR-867) and sixteen differentially expressed mRNAs related to energy metabolism including glycosylation, glucose metabolism process, carbohydrate metabolism process, fatty acid metabolism, and ATP binding.…”
Section: Discussionmentioning
confidence: 99%